Building Energy Sovereignty in Madura: Legal Analysis, Energy Crisis and Implementation of President Prabowo's Asta Cita - Lisan, Imam Fasichul; Wijaya, Dodik Pranata; Fathorrahman, Fathorrahman; Elkaffash, Mohamed; Barak, Ahmed Mohamed; Asyiqoh, Lin (Faculty of Law Universitas Trunojoyo Madura, 2026)
This study aims to analyze the legal orientation and future potential of the Nipah Reservoir in Sampang, Madura, within the framework of Indonesia’s energy transition and commitment to achieve Net Zero Emissions by 2060. The main contribution of this research lies in the proposal to reinterpret reservoirs that have historically been geared toward irrigation, raw water supply, and tourism, transforming them into renewable energy projects that support both national energy sovereignty and environmental sustainability. Using juridical-normative methods through legislative and conceptual approaches, this research was enriched with electrical engineering literature and primary data through interviews with the President Director of Perum Jasa Tirta I. The results of the study show that although the Nipah Reservoir is not listed in the PLN 2024-2033 or 2025-2034 RUPTL, it has significant potential to be developed into a Microhydro Power Plant (PLTMH) and/or a Floating Solar PV (Solar PV) plant. This utilization not only reduces Madura’s dependence on fossil-fuel electricity from Java but also helps achieve the target of a new renewable energy mix of 23% by 2025. This study concludes that the reinterpretation of the legal framework is essential to align old irrigation-oriented regulations with modern renewable energy policies. The recommendation of this study is that the government issue more comprehensive regulations and integrate the Nipah Reservoir into national energy planning as a model for locally based renewable energy development.